Effect of Colonoscopy Screening on Risks of Colorectal Cancer and Related Death - Bretthauer, Michael; Løberg, Magnus; Wieszczy, Paulina; Kalager, Mette; Emilsson, Louise; Garborg, Kjetil; Rupinski, Maciej; Dekker, Evelien; Spaander, Manon; Bugajski, Marek; Holme, Øyvind; Zauber, Ann G.; et al. (The New England journal of medicine, 2022)
In this randomized trial involving 84,585 participants in Poland, Norway, and Sweden, the risk of colorectal cancer at 10 years was lower among those invited to undergo screening colonoscopy than among those assigned to no screening.